Children no more than ‘little adults child labour as major consequence of the industrial revolution in Charles Dickens’ novel Oliver Twist - Hossain, Alamgir; Xiaoling, Gao; Rasool, Ushba (International Journal of Publication and Social Studies, 2023)
This article has attempted to highlight the importance of child labor, child misery, and social and economic changes in the Age of Industrialization as depicted in the novel Oliver Twist by Charles Dickens (1837–1839). The study utilizes the descriptive qualitative research method to analyze how Dickens portrays helpless children whose childhoods are taken away by harsh reality. “Industrial Revolution” refers to the change from rural and handcrafted lifestyles to an industrialized society built on manufacturing. Poor people moved from the countryside to the cities, where they lived in slums and crowded places due to the Industrial Revolution, negatively affecting their quality of life. During this time, children were excessively labored, working under challenging conditions for minimal pay. In this novel, Charles Dickens denounces how poor children were forced into labor, mistreated, exploited, and denied an education. He also criticized how the capitalist system, based on class distinctions, gave rise to villains who would do anything to stay at the top of their social level. Dickens has depicted the anguish of impoverished children in this novel, who were denied parental love and education while working long hours in unfavorable circumstances. The current study argued that child labor is the fundamental result of the industrial revolution with reference to previous literature and will be helpful for future researchers to get overall idea of later consequences.